Comparative Effects of Direct and Metalinguistic Computer-Mediated Feedback on L2 Learners’ Writing Ability and Willingness-to-Write - Mahmood Hashemian; Maryam Farhang-Ju (Journal of Modern Research in English Language Studies, 2022)
The present study investigated the probable effects of asynchronous direct and metalinguistic computer-mediated corrective feedback (CMCF) on the writing ability (WA) and willingness-to-write (WTW) of upper-intermediate L2 learners. To this aim, a convenient sample of 90 upper-intermediate L2 learners volunteered to participate in this study. In the next stage, they were assigned into 3 intact groups. Intact experimental groups received asynchronous direct CMCF and metalinguistic CMCF on the different aspects of their writings, whereas the control group did not receive any CMCF. To check the (probable) impact of asynchronous direct and metalinguistic CMCF on the participants’ WA, the researchers assessed the participants’ WA before and after the treatment. Furthermore, participants filled out a previously developed and validated WTW questionnaire before and after the treatment, which measured their WTW. In the last stage, 16 participants of the experimental groups were interviewed to provide an in-depth understanding of factors affecting the participants’ WTW. ANOVA results revealed that the participants’ WA significantly improved due to both asynchronous direct and metalinguistic CMCF, with no significant difference between the efficacies of the CMCF types. Besides, the results indicated that both CMCF types resulted in an improvement in the participants’ WTW. Furthermore, the theme analysis of interview findings suggested that the participants perceived CMCF to be facilitative. The interview results were in agreement with those of the quantitative analyses. The findings of this study may contribute to understating L2 learners’ needs and considering pedagogical decision-making for course developers and instructors.